Peatland formation, succession and carbon accumulation at a mid-elevation poor fen in Pacific Canada. (November 2019) - Lacourse, Terri; Adeleye, Matthew A; Stewart, Johanna R
We reconstructed peatland formation, succession and long-term rates of carbon (C) accumulation at a mid-elevation poor fen on Vancouver Island in coastal British Columbia, Canada. Multi-proxy paleoecological analyses including bulk chemistry, peat composition, macrofossils, pollen and non-pollen palynomorphs show terrestrialization starting from a small oligotrophic lake 14, 000 cal BP. Peat accumulation began by 11, 600 cal BP with the transition to an emergent Nuphar -dominated shallow-water marsh. Terrestrialization in the center of the peatland was more or less complete by 10, 400 cal BP with the development of a Sphagnum -dominated poor fen that continues to the present. Outward expansion by paludification appears to have brought the peatland close to its modern lateral extent by 10, 000 cal BP, suggesting that terrestrialization and paludification played important concurrent roles in the early development of this poor fen. Mean long-term rates of C accumulation (13 g C/m 2 /yr) are lower than at most Northern Hemisphere peatlands including nearby lowland bogs. Maximum rates of 43 g C/m 2 /yr occurred in the early Holocene during accumulation of Nuphar peat and the transition to Sphagnum peat and coincided with high summer temperatures and increased seasonality, which promote growing season productivity and reduce winter decomposition. Early Holocene increases in C accumulation rates occurred at two nearby lowland bogs during similar wetland stages. Collectively, these studies demonstrate that climate and autogenic succession, including changes in relative water table depth and plant functional groups, interacted to drive Holocene peatland dynamics and C accumulation rates in the maritime setting of coastal British Columbia.